MODERN METHODS OF COMMUNICATION FOR AN EFFECTIVE EDUCATION - Peri annan, Sebastian (Journal of Dharma, 2006)
The other day when my 5 year old niece spoke in her not-so-perfect English, I tried playing teacher and corrected her. Guess what she did? She looked straight into my eyes and said, “You did understand what I said, didn’t you?” This incident made me realise that communication is all about getting the message across. With all due respect to my English teacher, the essence of communication is in the message, not so much the words. The Readers Digest once contained this story about a ninth-grade health class: it was a class in which from the first day onwards the blackboard was covered with the names and locations of the major bones and muscles of the human body. The diagram stayed on the board throughout the term, although the teacher never referred to it. On the day of the final exam, the students came to class to find the board wiped clean. The sole test question was: “Name and locate every major bone and muscle in the human body.” The class protested in unison: “We never studied that!” “That’s no excuse,” said the teacher. “The information was there for months.” After the students struggled with the test for a while, he collected the papers and tore them up. “Always remember,” he told them, “that education is more than just learning what you are told.”